The role of Environment Management Agency towards sustainable environment management in Zimbabwe: a case study of Gweru district - Mavela, Nosimilo (Midlands State University, 2014)
This research’s main objective was to assess the contribution of EMA in sustainable environment management in Gweru District. It was realized that if there is poor service delivery in terms of sustainable environment management, health, economy, people, and environment is threatened through degradation of the environment, spread of diseases, conflicts in regard to the environment, extinction of natural resources thus causing underdevelopment. The research targeted EMA and its stakeholders like mines, schools, industries, members of the public and conducted interviews as well as used observations. Responses from respondents illustrate that they are aware of the threats to the environment thus undermining development in all sectors be it the economic, social or political sphere. The researcher recommends that EMA manages to monitor closely its stakeholders at the same time concentrate on dissemination of information more to members of the public thereby promoting a grassroots approach to environment management., I also recommend the public and stakeholders to practice friendly environment management systems so that sustainable development is achieved .